IMPORTANCE OF CHILD EDUCATION IN PRESCHOOL PEDAGOGY (American Journal of Interdisciplinary Research and Development, 2022)
Nowadays it is becoming much more important to take of children not only his future but also morality as well. Pedagogy has absorbed all the original pedagogical ideas of the past in the process of development of pedagogy, and the experience of pedagogy of the country and abroad has taken advantage of all new aspects. It will be discussed about the importance of child education in preschool pedagogy.